Understanding the relationship between traumatic suffering, posttraumatic growth, and prosocial variables. Issue 7 (26th October 2021) - El-Gabalawy, Renée; Mackenzie, Corey S.; Starzyk, Katherine B.; Sommer, Jordana L.
Abstract: Objective: We investigated facets of posttraumatic growth (PTG) theory, including the nature of the index event, the relationship between suffering and PTG, and prosocial correlates of PTG. Methods: Undergraduate students ( N = 253) completed measures of PTG and trauma-related, psychopathology/affect, and prosocial correlates. Results: Differences emerged in PTG according to event severity, with greater PTG for those who experienced a trauma compared to a stressor. PTG was associated with nearly all trauma-related, select psychopathology/affect (e.g., anxiety, positive affect) and prosocial (e.g., empathy, volunteerism) variables. In a multivariable model, race/ethnicity, helpfulness, perceived chronicity of distress, and positive affect were associated with PTG. Curvilinear trends demonstrated that moderate chronicity of distress and current emotional distress from trauma were associated with the greatest PTG. Conclusions: Findings highlight factors associated with growth, including a moderately distressing trauma, positive affect, and prosocial behavior. Results clarify PTG theory and contribute to understanding conflicting evidence in prior PTG literature.